Study on reasonable production allocation method of tight sandstone gas reservoir—A case of XX block in ordos basin - LV, Min; CUI, Hongjun; LEI, Yanyun; Lei, Kaiyu; ZHU, Yushuang (Frontiers in Energy Research, 2023)
Reasonable production allocation of tight sandstone gas reservoirs is an important basis for efficient development of wells. Combining multiple mathematical models, the modified flowing material balance equation was established considering the variation of viscosity and compressibility, and a reasonable production allocation process was developed. The results show that : ① The flow material balance method ignores the change of compressibility, viscosity and deviation coefficient in the calculation. Compared with the results calculated by the material balance method, the results of the flow material balance method are smaller. ② A modified flowing material balance method is established, verified by the production of 670 wells in the study area during stable period. Compared with the open flow rate method, the error of dynamic reserve allocation method is smaller, with an error of 0.07 %. ③ When dynamic reserves are used to allocate production, the initial decline rate of wells is reduced by 74.65 % on average, the production on stable period increases by 21.28 %, and the time increases by 1.79 %. This study provides support for dynamic reserve calculation and reasonable production allocation of gas wells in the study area, and has important guiding significance for the formulation of reasonable development plan and economic and efficient development of tight sandstone gas reservoirs.